Emergence of Leaf Spot Disease on Leafy Vegetable and Ornamental Crops Caused by Paramyrothecium and Albifimbria Species - Matić, Slavica; Gilardi, Giovanna; Gullino, Maria Lodovica; Garibaldi, Angelo (Phytopathology, 2019)
The genera Paramyrothecium and Albifimbria have been established from the former genus Myrothecium and they generally comprise common soil-inhabiting and saprophytic fungi. Within these genera, only two fungi have been recognized as phytopathogenic thus far: P. roridum and A. verrucaria, both of which cause necrotic leaf spots and plant collapse. Severe leaf necrosis and plant decay have been observed in Northern and Southern Italy on leafy vegetable crops. Thirty-six strains of Paramyrothecium- and Albifimbria-like fungi were isolated from affected plants belonging to eight different species. Based on morphological characteristics, 19 strains were assigned to A. verrucaria, whereas the remaining strains, which mostly resembled Paramyrothecium-like fungi, could not be identified precisely. Molecular characterization of six loci (internal transcribed spacer [ITS], β-tubulin [tub2], calmodulin [cmdA], translation elongation factor 1-alpha [tef1], large subunit ribosomal RNA [LSU], and mitochondrial ATP 6synthase 6 [ATP6]) of the 36 new isolates and three previously ITS-characterized isolates assigned all strains to four species: A. verrucaria, P. roridum, P. foliicola, and P. nigrum. Single and concatenated phylogenetic analyses were conducted, and they clearly distinguished the isolated fungi into four different groups. A. verrucaria, P. roridum, P. foliicola, and P. nigrum were able to induce leaf necrosis singly, and they were confirmed to be the causal agents of the leaf spot disease through pathogenicity assays. The involvement of fungi previously considered saprophytic (i.e., P. foliicola and P. nigrum) in the development of plant disease for the first time deserves particular attention because of the possibility of their transmission by seeds and the limited knowledge of their management with chemicals.